YOUR HEALTHY SMILE: DENTAL HEALTH EDUCATION IN AN EFFORT TO CHANGE BEHAVIOR IN THE CORRECT WAY OF BRUSHING YOUR TEETH - Puspita, Enny; Puspita, Sylvie; Putra, Kusuma WIjaya Ridi; Zatihulwani, Eliza Zihni; Rustanti, Elly (Journal of Indonesian Public Health Service, 2024)
Introduction to dental hygiene at an early age is very important. This is because dental health will be able to improve the overall quality of health of children. The aim of carrying out this community service activity was to train pre-school children in brushing their teeth properly and correctly, so that they are able to do it independently. This activity was carried out at An-Nur Kindergarten, Peterongan, Jombang with the target being all 150 students at An-Nur Kindergarten, Peterongan, Jombang. This community service activity was carried out on May 27, 2024. Preparations for this community service activity were carried out 2 weeks beforehand, starting from the process of preparing the activity to applying for permits and preparing the materials to be provided. As a form of final evaluation, the activity was attended by 150 students, where the students participated in the activity enthusiastically. The implementation of these community service activities ran on time and smoothly.